An Analysis of Translation Techniques of Interrogative Sentence in Maleficent Mistress of Evil 2019 Movie Subtitle - Novika, Restu; Zaim, M (Universitas Negeri Padang, 2024)
This research conducted to analyze the translation techniques used in translating interrogative sentence in Maleficent Mistress of Evil 2019 movie subtitle. The purpose of this research in to find the type of translation techniques used in translating interrogative sentence in the movie. This research used theory Azar (2002) to identify interrogative sentence and theory Molina and Albir (2002) to identify translation technique. This research is descriptive qualitative research. The data were gathered from the subtitle of interrogative sentence in the movie. There are 88 data of interrogative sentence found in the movie. There were 11 types of translation techniques used in translating interrogative sentence in the movie, there were reduction with 18 data, establish equivalent with 14 data, linguistic compression with 14 data, literal translation with 14 data, calque with 12 data, discursive creation with 6 data, generalization with 3 data, modulation with 3 data, amplification with 2 data, transposition with 1 data and variation with 1 data. The results of data analysis show that the dominant type of translation technique in translating interrogative sentence is reduction with 18 data.